Impact of inhibition of the renin-angiotensin system on early cardiac and renal abnormalities in Sprague Dawley rats fed short-term high fructose plus high salt diet - Siddiqui, Sharif Hasan; Pitpitan, Rebekah; Boychev, Boycho; Komnenov, Dragana; Rossi, Noreen F. (Frontiers in Nutrition, 2024)
The combination of a high fructose and high salt diet typical of western diet induces high blood pressure, aortic stiffening, left ventricular (LV) diastolic dysfunction and impaired renal function in rodents. Despite an activated renin-angiotensin system (RAS) in rats fed high fructose and high salt, acute inhibition of the RAS pathway does not improve cardiac and vascular parameters. It may well be that longer term treatment is required to permit remodeling and improve cardiovascular function. Thus, we hypothesized that chronic RAS inhibition fructose+high salt-fed rats to restore blood pressure (BP) to levels similar to glucose plus normal salt-fed controls will improve cardiorenal function and histopathology. Male and female Sprague Dawley rats monitored by hemodynamic telemetry were fed 0.4% NaCl chow during baseline, then changed to chow containing either 20% glucose+0.4% NaCl (G) or 20% fructose+4% NaCl (F) and treated with vehicle, enalapril (Enal, 4 mg/kg/d) or losartan (Los, 8 mg/kg/d) by osmotic minipump for 25-26 days. BP was elevated in the fructose+high salt groups of both sexes (P < 0.05) and restored to control levels by Enal or Los. Pulse wave velocity (PWV) was lower in female F+Los rats and cardiac output higher in female F+Enal rats. GFR was not changed by diet or treatment. Fructose+high salt groups of both sexes displayed higher albuminuria that was decreased by Enal in male rats. Cardiac fibrosis and mesangial hypercellularity were greater in fructose+high salt-fed rats of both sexes and improved with either Los or Enal. Thus, inhibition of the RAS improves early changes in cardiac and renal histopathology in both sexes and albuminuria in male rats fed high fructose and high salt diet. Functional improvements in cardiorenal parameters may require longer treatment.